If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 2 = 9 Reorder the terms: 2 + 3n = 9 Solving 2 + 3n = 9 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3n = 9 + -2 Combine like terms: 2 + -2 = 0 0 + 3n = 9 + -2 3n = 9 + -2 Combine like terms: 9 + -2 = 7 3n = 7 Divide each side by '3'. n = 2.333333333 Simplifying n = 2.333333333
| 2x=3(1-x)-(x-1) | | 2x^3-12x^2+24x-2=0 | | 3x-(x-2)=(2x-1)(-3x+9) | | (2x-1)(-3x+9)=0 | | 2(c-2)whenc=7 | | 3x-1=4(2x-5) | | 63-4x=5x+23 | | 0.4(3k-0.6)= | | 13-9x=73-23x | | 0.05x-.6=5.3 | | 5p-6+3p=12 | | 13h+6d-9d-7h=0 | | (4x-37).12=276 | | 3(d-8)-6=9(d+2) | | -17-4x=-7-7x | | x^2+2y^2=1 | | 0.5(8+2)=17 | | 11=-4(x+1) | | f=35r^2 | | 3*x-5=34 | | 38x-5=34 | | -6x-3=12-x | | 8-8x=4x-16 | | |x|-4=9 | | 4=-4(x-1) | | 27x+12y-2561=0 | | -12x-15=-123 | | -8+(-4)+5= | | 100+(-30)= | | 88x^2-97x+24=0 | | 88x^2-97+24=0 | | -15+-6= |